Carnival at Candlelight: Magic Tree House "Merlin Missions" #5 - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2005)
While on a mission to prove to Merlin that they can use magic wisely, Jack and Annie travel to seventeenth-century Venice, Italy, to save the city from disaster.
"A Merlin mission."
"A Stepping Stone book."
Keywords: Tree houses -- Fiction; Brothers and sisters -- Fiction; Time travel -- Fiction; Magic -- Fiction; Venice (Italy) -- History -- 17th century -- Fiction; Italy -- History -- 17th century -- Fiction